The associations of Tibetan Plateau spring snow cover with East Asian summer monsoon rainfall before and after 1990 - Wijngaard, René Reijer; Oh, Hyoeun; Khanal, Sonu; Yoon, Arim; van de Berg, Willem Jan; An, Soon-Il (Frontiers in Earth Science, 2024)
This study assesses the associations of spring snow cover variations at the Tibetan Plateau (TP) with East Asian summer monsoon (EASM) rainfall before and after 1990. The outcomes suggest that the snow-monsoon relationship changes from partly negative to positive over all regions of the TP from 1968-1990 (P1) to 1991-2019 (P2). Composite analyses reveal that the changing snow-monsoon relationship can be associated with different wave train patterns ensuing from changes in background zonal wind and meridional temperature gradients. In P1, high snow cover can be associated with an anomalous cyclone southwest of the TP in spring, which persists in the following summer, partly due to the underlying snow cover. The anomalous cyclone accompanies downstream anomalies over East Asia, which form a strong east-west oriented wave pattern and induce northerly inflow of dry air over East Asia, reducing rainfall over the northern EASM domain. In P2, an anomalous cyclone over the western TP weakens and loses its significance in May-June and summer, which may partly be attributable to a decline in snow forcing. Southeastward propagation of wave energy in May-June initiates the formation of an anomalous anticyclone over southeastern China and the western North Pacific. Concurrently, a meridional circulation develops over East Asia, which enhances southwesterly moisture inflow, resulting in increased EASM rainfall. This research contributes to an improved understanding on the changing snow-monsoon relationship.